Structure and expression of the gene coding for the alpha-subunit of DNA-dependent RNA polymerase from the chloroplast genome of Zea mays. - Ruf, M (Nucleic Acids Res, 1988)
The rpoA gene coding for the alpha-subunit of DNA-dependent RNA polymerase located on the DNA of Zea mays chloroplasts has been characterized with respect to its position on the chloroplast genome and its nucleotide sequence. The amino acid sequence derived for a 39 Kd polypeptide shows strong homology with sequences derived from the rpoA genes of other chloroplast species and with the amino acid sequence of the alpha-subunit from E. coli RNA polymerase. Transcripts of the rpoA gene were identified by Northern hybridization and characterized by S1 mapping using total RNA isolated from maize chloroplasts. Antibodies raised against a synthetic C-terminal heptapeptide show cross reactivity with a 39 Kd polypeptide contained in the stroma fraction of maize chloroplasts. It is concluded that the rpoA gene is a functional gene and that therefore, at least the alpha-subunit of plastidic RNA polymerase, is expressed in chloroplasts. IMAGES: